2021
DOI: 10.1017/s0373463320000739
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of professional commitment for Chinese new generation cohorts in a sample of seafaring officers

Abstract: This study aims to examine the predictors of professional commitment of the Chinese new generation, divided into post-80s and post-90s cohorts. A questionnaire survey was employed to collect data from Chinese seafaring officers of these cohorts. The results through hierarchical regression analysis present the two cohorts as having both similar and different predictors. The main difference is that company management and policies positively drive the post-80s cohort to work at sea but not the post-90s. The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…(2019) showed that career adaptability influences turnover attempts, but both career satisfaction and perceived organisational support mitigate the effect of poor career adaptability on turnover intention. Employment status, family income, achievement motivation, perceived security, and work ethic are identified as key elements with significant impacts on the professional commitment of young officer seafarers (Jia, 2021).…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…(2019) showed that career adaptability influences turnover attempts, but both career satisfaction and perceived organisational support mitigate the effect of poor career adaptability on turnover intention. Employment status, family income, achievement motivation, perceived security, and work ethic are identified as key elements with significant impacts on the professional commitment of young officer seafarers (Jia, 2021).…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Professional commitment implies the affinity of individuals with their profession and their motivation to stay with the job (Gallagher and Parks, 2001). Literature highlights several factors that may affect professional commitment, including some demographic characteristics, workplace situation and job characteristics (Freund et al, 2013;Han et al, 2020;Jia, 2021;Zheng et al, 2021). Professional commitment is vital for healthcare professionals and workers, which determines their lifelong learning and the future of their profession.…”
Section: Introductionmentioning
confidence: 99%